Transmission Lags and Optimal Monetary Policy - Alessandro Flamini (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
Real world monetary policy is complicated by long and variable lags in the transmission of the policy to the economy. Most of the policy models, however, abstracts from policy lags. This paper presents a model where transmission lags depend on the behaviour of a two-sector supply side of the economy and focuses on how lag length and variability affect optimal monetary policy. The paper shows that optimal monetary policy should respond more to the sector with the shortest transmission lag and that the presence of production links among sectors amplifies this response. Furthermore, the shorter or more variable the aggregate transmission lag, the more active the overall policy and the larger the response to the sector with the shortest transmission lag. Finally, the relative strength of the response to inflation and output gap depends on the intensity of the sectoral production links, and on the length of the transmission lags. Only with reasonable production links should the optimal policy respond more to in?ation than to the output gap in line with the empirical evidence.
Keywords: E52; E58; F41; 330; Inflation targeting; monetary policy transmission mechanism; policy transmission lags; multiplicative uncertainty; Markov jump linear quadratic systems; optimal monetary policy